Experiences of women in sport leadership: The case of Zambia - Phiri, Tomaida (Πανεπιστήμιο Πελοποννήσου, 2016)
Research studies on women leaders have been on the increase over the last few years. It is, however, worth noting that research on African women in leadership is not fully developed or done despite the exemplary performance of African women in sports over the past number of years. To a large extent, African women in sports leadership remain rare or invisible. Therefore, this study endeavoured to examine experiences of women in sport leadership in Zambia. A number of women leaders including Physical Education (PE) teachers, pupils and sport administrators were selected from various institutions, organizations and education institutions in Kabwe and Lusaka districts of Zambia. These responses were examined as they relate to their socialization, education and training, work and family lives, the challenges experienced, and how they are able to negotiate these in a male dominated world. This study is built on the 2004 International Olympic committee and Institute of Sport, Leisure Policy study on the women in National Olympic Committee (NOCs) from different nations around the world. It has highlighted important roles that women sports leaders play in the development of sports. The researcher hopes that the findings from the study will influence the National Sports Council policy in Zambia, helping to create more opportunities for women and girls as participants and leaders in sport, operating in line with the ‘Sport For All’ mandate of the International Olympic Committee (IOC), whose, among other purposes, is to promote active lifestyles and assisting in the crafting of legislative policy directives to augment promotion of women to position of leadership in sports.
Keywords: Αθλητική ηγεσία; Γυναίκες - Αθλητισμός - Ηγεσία; Αθλητική ηγεσία - Ζάμπια; Sport leadership; Women - Sports - Leadership; Sport leadership - Zambia